Implementasi Kombinasi LOPCOW dan Operational Competitiveness Rating Analysis Dalam Rekomendasi Tempat Wisata Indoor - Setiawan, Gde Denny; Octaviansyah Pasaribu, A. Ferico (JUSTINDO (Jurnal Sistem dan Teknologi Informasi Indonesia), 2024)
Indoor attractions offer an exciting and comfortable holiday experience, especially for those who want to avoid extreme weather or want indoor comfort. The selection of indoor attractions is often faced with various problems involving distance, price, rating, and cleanliness. All these factors must be carefully considered to ensure that the chosen indoor attraction can provide a satisfying and enjoyable experience. The application of a combination of Logarithmic Percentage Change-Driven Objective Weighting (LOPCOW) and Operational Competitiveness Rating Analysis (OCRA) in the performance evaluation of business alternatives offers an innovative and robust approach to decision making. LOPCOW allows objective determination of criteria weighting based on logarithmic percentage changes, emphasizing the dynamics of relative performance changes between criteria. Integration with OCRA, which evaluates operational competitiveness through efficient ratio analysis. The ranking results showed that the first best rank was obtained by Puncak Mas with a final value of 1.2596, the second-best rank was obtained by Wira Garden with a final value of 1.1607, the third best rank was obtained by Lampung Walk with a final value of 1.0289. The combination of these two methods increases the accuracy and reliability of ranking results, assisting decision makers in choosing truly superior alternatives based on relevant and up-to-date data. By utilizing data-driven analysis and robust methodologies, the decision-making process becomes more efficient and can be done faster, saving time and resources.